2016
DOI: 10.1071/hc15018
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder pain in primary care: frozen shoulder

Abstract: BACKGROUND AND CONTEXT: Frozen shoulder is a painful condition that follows a protracted clinical course. We aim to review the management of patients with a diagnosis of frozen shoulder who are referred for specialist orthopaedic evaluation against existing guidelines in primary care. ASSESSMENT OF PROBLEM:Referrals and clinical records were reviewed for all patients referred for orthopaedic specialist assessment who received a specialist diagnosis of frozen shoulder. Diagnostic, investigation and management p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…[4–6] It has been reported that this condition can affect 2% to 5% of the general population, mostly among the female population between 40 and 65 years old. [711] A variety of studies tried to explore its mechanism. [1214] Unfortunately, it is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[4–6] It has been reported that this condition can affect 2% to 5% of the general population, mostly among the female population between 40 and 65 years old. [711] A variety of studies tried to explore its mechanism. [1214] Unfortunately, it is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound scan or imaging were the most commonly investigations made. So when they treated once the diagnosis made according to the standard clinical guidelines then their patients came with significant clinical difference and the functional improvement [22]. So we concluded that general practitioners refer their patients to the physiotherapist and generally they recommend the x-ray for investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Frozen shoulder, or adhesive capsulitis, is a painful and disabling condition of unknown etiology caused by a spontaneous contracture of the glenohumeral joint in absence of an evident previous event, resulting in reduction of joint motion [71]. This debilitating condition affects from 2 to 5% of the general population [72] and its prevalence increases to 10-38% in patients with comorbidities, such as hypothyroidism [73], diabetes, increased body mass index and cervical spondylosis [74].…”
Section: Frozen Shouldermentioning
confidence: 99%